Being a foster family in Portugal - motivations and experiences - Diogo, Elisete (2021)
Foster care is an almost absent component in the child care system and scientific research conducted in Portugal foster comprises 3.2%(1) of out-of-home care in Portugal. This research aims to contribute to a deeper visibility of the care phenomena, giving specific attention to the foster families themselves. This research adopted a qualitative analytical approach, inspired by Grounded Theory. Foster families' motivation is rooted in altruism, affection for children, and sensitivity to maltreatment. Personal and professional biography or past contact with out-of-home care can also induce predisposition to become a carer. The experience of being a carer(2) is one of traversing through a life of many challenges and rewards. Considering the recognition from the stakeholders, it is a rewarding task. The quality of the service provided and the performance of the care professionals are both key elements to foster care.